Faktor-Faktor yang Mempengaruhi Kelelahan Kerja Pada Tim Relawan Covid-19 Di Kota Binjai - Malau, karina Br; SKM,M.Kes, Eliska (Jurnal Kesehatan Ilmiah Aufa Royhan, 2020)
The increase in data confirmed by the coronavirus virus continues to increase, resulting in a lot of pressure on all health workers and the covid-19 volunteer team. The pressure that occurred on the volunteer team partly experienced fatigue where the highest argument was the use of PPE completely and the number of procedures, the discomfort when wearing PPE was very tired, coupled with the environment with hot weather. So the factors that cause fatigue in the volunteer team are age, gender, working period, work shift, physical environment, and the length of time using PPE. The research approach method is a combined method of quantitative and qualitative or a mixed method approach. This research was conducted at the main Covid-19 post in the city of Binjai by taking samples at the keyperson for the interview stage. This qualitative research instrument is the researcher himself who adheres to the questionnaire guidelines conducted face-to-face. The data analysis technique is the analytic descriptive technique. The purpose of this study was to look at the factors that influence fatigue in the Covid-19 volunteer team in the city of BinjaiKey words: Fatigue factor, volunteers